PENGARUH PENGANGGARAN PARTISIPATIF, LOCUS OF CONTROL DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Febriana, Rahma; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the influence of participation of budget preparation, locus of control and organization commitment to the managerial performance with case study in Local Apparaturs Working Unit (SKPD) of Surabaya city. This research is quantitative research. The data collection method has been done by using survey method. The data is the primary data which has been obtained by issuing questionnaires to the respondents. The sample collection method has been done by using purposive sampling. The numbers of research samples are 66 respondents. Meanwhile, the analysis technique has been carried out by using multiple linear regressions analysis and the SPSS (Statistical Product and Service Solutions) 20.0 version. Based on the result of the hypothesis test in this research, it shows that: the participation of budget preparation gives positive influence to the managerial performance with test result has significance value 0,000 < 0,05, locus of control gives positive influence to the managerial performance with test result has significance value 0,001 < 0,05 and organization commitment gives positive influence to the managerial performance with test result has significance value 0,016 < 0,05.Keywords: Participation of budget preparation, locus of control, organization commitment, managerial performance.